2004
DOI: 10.1001/archotol.130.4.423
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Sinus Computed Tomography on Treatment Decisions for Chronic Sinusitis

Abstract: To determine the impact of sinus computed tomography (CT) on treatment decisions by otolaryngologists and to explore the factors leading to choice of surgical treatment for patients suspected of having chronic sinusitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
6

Year Published

2006
2006
2016
2016

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 23 publications
0
20
0
6
Order By: Relevance
“…Rak KM et al 17 In addition to that ,the mucosal thickening of sinuses has been reported in patients with nonspecific upper respiratory tract infection, such as the common cold and coryza. Gwaltney Jr et al there have been numerous reports in surgical journals that found sinus CT findings did not correlate well with a patient's clinical symptoms, since results of sinus CT can be normal for severely symptomatic patients and abnormal for patients with minimal symptoms Anzai Y et al 18,19 Shwartz R 2010 describes CT findings in primary nasal and nasopharyngeal rhinoscleroma include soft-tissue masses of variable sizes. The lesions are characteristically homogeneous and nonenhancing, and they have distinct edge definition.…”
Section: Figure 10: Classification Of Cases On the Basis Of Nasal Patmentioning
confidence: 99%
“…Rak KM et al 17 In addition to that ,the mucosal thickening of sinuses has been reported in patients with nonspecific upper respiratory tract infection, such as the common cold and coryza. Gwaltney Jr et al there have been numerous reports in surgical journals that found sinus CT findings did not correlate well with a patient's clinical symptoms, since results of sinus CT can be normal for severely symptomatic patients and abnormal for patients with minimal symptoms Anzai Y et al 18,19 Shwartz R 2010 describes CT findings in primary nasal and nasopharyngeal rhinoscleroma include soft-tissue masses of variable sizes. The lesions are characteristically homogeneous and nonenhancing, and they have distinct edge definition.…”
Section: Figure 10: Classification Of Cases On the Basis Of Nasal Patmentioning
confidence: 99%
“…A Tomografia Computadorizada de Feixe Cônico (TCFC) é uma técnica precisa quando utilizada na detecção de lesões simuladas em todas as superfícies do seio maxilar, podendo ser usada para diagnóstico dessa região. A tomografia computadorizada tem sido considerada o padrão ouro no diagnóstico radiográfico de seios maxilares em crianças e adultos, sendo largamente utilizada para a avaliação de patologias sinusais, embora a técnica seja questionada por alguns autores pela sua falta de especificidade 4,6,7 . Devido à localização anatômica do seio maxilar, se relacionando com estruturas nobres, como a base do crânio, encéfalo, assoalho da órbita, etc, o seu envolvimento em patologias deve ser cuidadosamente avaliado, pois danos nas estruturas relacionadas a ele são graves e as infecções podem se propagar local ou sistemicamente, o que torna a avaliação destes, durante o exame tomográfico da maxila, de valor inestimável 1,8 .…”
Section: Resultsunclassified
“…Atualmente, a Tomografia Computadorizada por Feixe Cônico (TCFC) se tornou amplamente utilizada para o diagnóstico na região dento-maxilo-facial, sendo indicada como uma técnica precisa no exame de lesões orais e maxilo-faciais, devido às suas excelentes resoluções anatômicas 2-4 . Esse sucesso é principalmente devido à obtenção de imagens volumétricas que permitem a visualização e o estudo das lesões de forma tridimensional [4][5][6] . Desta maneira, o objetivo desta pesquisa foi avaliar os achados tomográficos fortuitos em seios maxilares em exames de TCFC, assim como a sua correlação com a sintomatologia clínica relatada pelos pacientes.…”
Section: Resultsunclassified
See 2 more Smart Citations